Sintesis Ï-mentana-3,8-diol dan Aplikasinya sebagai Gel Air Freshener Penolak Nyamuk Aedes aegypti - Syafi'i, Imam; Cahyono, Edy; Mahatmanti, F. Widhi; Alighiri, Dante (Indonesian Journal of Chemical Science, 2020)
Ï-Menthane-3,8-diol (PMD) has been synthesized from citronellal with citric acid catalyst through a cyclization process by stirring and heating. Citric acid is used as a substitute for sulfuric acid in PMD because it is cheap, safe and is an effective alternative to synthesis. The result of PMD synthesis from citronellal by 5 g citronellal; 7 g of citric acid solution 10%; for 8 hours stirring at 50o temperature were obtained 71.15% yield; 100.00% conversion; and 71.15% selectivity. PMD gel air freshener is made using PMD then formulated with carrageenan as a gelling agent with PMD variations. The higher PMD content in gel increase the water holding capacity. The best mosquito repellent strength was obtained from PMD gel with 15% PMD which has the greatest mosquito repellent strength in 60 minute (65.00%).